"عبد الحليم شرر رائد الرواية التاريخية "راوية فتح الأندلسAbdul Halim Sharar, the Pioneer of the Historical novel “The Rawiah of the Conquest of Andalusia” (Al-Qamar, 2021)
The historical novel is considered an important literary form because it provides assistance in studying the history. There is a great relationship between history and the historical novel, despite the different ways of studying it. The history is based on facts, while the novel is based on imagination. Abdel Halim Sharar in his narratives works focus on Islam and cultural and literary balance in his fiction works. Abdul Halim Sharar is considered the Dean of the Urdu Historical novel, and distinguished his work and wrote distinguished Islamic literature, where he laid the foundation for the art of historical novel. In this paper the researcher work seek to find out the narrative techniques of writer in his Historical novel. And how Abdel Halim Sharar create a new image among the Muslim youth through his work.
Keywords: Islamic issues; history; Muslim youth; conciliation